Determination of the Common Risk Factors Associated with Road Traffic Accidents in Iraqi Kurdistan Region - Qader, Delan J. (Sulaimani Journal for Pure and Applied Sciences, 2022)
Increased traffic crashes have been one of the main issues local authorities have experienced due to the increased stability and economic development in Iraq’s Kurdistan region. Any residual risk by collisions that originate from, finish with, or involve a vehicle either partially or completely on a public road is considered a road traffic accident. The present study has been conducted to assess factors associated with road traffic accidents in the Kurdistan region. An investigation was carried out among drivers in the three provinces of Kurdistan. The data collection process was conducted from February 1–March 3, 2021, and was obtained from 1,427 drivers. The questionnaires were constructed according to the study’s objectives: sociodemographic data, driver’s behaviors, weather effects on road traffic accidents, and effects of car lights on road traffic accidents. Data have been gathered using a contracted questionnaire, conducted independently and anonymously. The questionnaire enquires about the risk factors and the situations which might cause predisposition to road traffic accidents and driving behaviors, as well as demographic data and driving style. The majority of the data was gathered from electronic surveys. More than half (74.5%) of the study sample are male; most of them (75.11%) use a seat belt while driving, 4.2% of drivers drink alcohol while driving, and 55.8% of drivers use a mobile phone while driving. Traffic accidents have impacted 9.46% of drivers due to weather conditions, 6.3% of drivers do not have driving licenses, and there is a highly significant association between age and gender with road traffic accidents. Several risk factors that apply to the general population are especially pertinent and even increased among young drivers: drunk driving, speeding, and lack of seat belt use. The study recommends that drivers be encouraged to drive defensively and obey traffic rules and regulations in all circumstances. This can be accomplished by increased traffic awareness and the enforcement of traffic regulations. Furthermore, cities should be equipped with public transportation modes such as trams or trains.
Keywords: Road traffic Accident; Risk factor; Injury; Driving behavior